Role of Trainings to rural masses in value addition of arid fruits and vegetables (Indian Journal of Arid Horticulture, 2025)
Horticultural produces grown in arid region are of explicit quality with great nutritional, medicinal, organo- leptic and economic importance. Some of the arid veg- etables like kachri, mateera, clusberbean etc. and fruits such as ker, khejri, ber, lasora, guarpatha and aonla, etc. on barren lands are available to the rural masses to provide food and nutrition security. Most of the arid food resources are available in plenty during a particular season, but all cannot be utilized to the fullest extent due to many rea- sons. Thus people residing in arid areas hardly get on con- siderable advantage from the abundantly available re- sources. Rural masses consume these food resources as such available to them in the form of simple vegetable or by simply in the form of dehydrated product or fruits are consumed in raw form. However, there is much scope in evolving the techniques of value addition and providing market to such underutilized commodities for more net re- Lurns. Various standardized techniques are practiced commercially for processing of arid fruits and vegetables (Table 1).
Keywords: vegetables; kachri